Teknologi pembelajaran: konsep dan aplikasinya untuk pembelajaran Pendidikan Kewarganegaraan - Abdul Gafur (Jurnal Civics: Media Kajian Kewarganegaraan, 2009)
Information and communication technology (JeT) is a systematic process of the design, development, utzlization, management, and evaluation of the process and resources for learning. These concept and principles can be used to solve the instructional problems including in the area of civics education. The implementation should be focused on the message (the curriculum of civics education), personnel (teachers, students, and administrative supports), hardware, software, management, and setting. The systematic strategy in implementating leT consists of five steps: design, development, utilization, management, and evaluation of the process and resources  of civics education.